Anomalies in the surface electronic structure of Cr. (November 2015) - Ali, Khadiza; Varier, Shyama R.; Biswas, Deepnarayan; Kandukuri, Srinivas C.; Maiti, Kalobaran
Abstract: We studied the electronic structure of high quality Cr(110) films grown on the W(110) surface employing angle resolved photoemission spectroscopy (ARPES). Experimental spectra from differently aged samples exhibit distinct signatures of the surface and bulk character of the features in the electronic structure. We observe that oxygen content on the surface gradually increases with aging and the hybridization of the adsorbed oxygens with the surface Cr atoms is significantly strong at temperature around room temperature or higher. The energy bands exhibit signature of band folding due to the spin density wave transition. In addition, a weakly dispersive sharp feature is found to emerge near the Fermi level at low temperatures presumably due to the correlation induced effects. Abstract : Highlights: Identified unambiguously the surface and bulk features in the electronic structure. Discovered signature of surface spectral weight transfer leading to a growth of a new surface feature at the Fermi level at low temperatures. The adsorbed oxygens' states hybridize significantly with the surface states of Cr at temperatures close to room temperature or higher, while they remain almost unreacted at low temperatures. We show that electron correlation is important in deriving the electronic properties of this system.